CRITICAL PERIOD OF MUNGBEAN (PHASEOLUS RADIATUS L.) TO WEED COMPETITION - I.H. UTOMO (BIOTROPIA, 1989)
A  field  experiment was  conducted  to  study  the  critical  period  of weed  control  on  the  crop  of mungbean (Phaseolus radiatus L.). The studies were done in the field of BIOTROP Experimental Station with  the  natural  existing weed  population.  It was  found  that  the  critical  period  of mungbean  to weed competition was from 3-6 weeks after planting.